Subarachnoid Hemosiderosis and Superficial Cortical Hemosiderosis in Cerebral Amyloid Angiopathy - Linn, J.; Herms, J.; Dichgans, M.; Brückmann, H.; Fesl, G.; Freilinger, T.; Wiesmann, M. (American Journal of Neuroradiology, 2008)
SUMMARY: Cerebral amyloid angiopathy (CAA) is an important cause of intracerebral hemorrhage. Its definite diagnosis still requires histopathologic demonstration of vascular amyloid. Thus, further improvement of noninvasive imaging methods would be desirable. Here we present 3 patients with histologically proved CAA, in which superficial cortical hemosiderosis and subarachnoid hemosiderosis were present in T2*-weighted MR images. Thus, we propose that these 2 findings might be valuable as noninvasive diagnostic markers for CAA.